A low‐profile sequential‐phase fed circularly polarized array antenna with an irregular ground. Issue 12 (4th October 2022) - Zhang, Xiaoyan; Yin, Lini; Li, Ziao; Hu, Yuxu
Abstract: Grooving or subtracting a projection of the antenna on the ground is one of the effective methods to both improve the axial‐ratio (AR) bandwidth and impedance bandwidth of a circularly polarized (CP) antenna. A bidirectional radiation, meanwhile, can be produced. Unfortunately, these methods will result in a decrease in the gain of the antenna due to a reduction of its ground size. To solve this issue, a conductive plane or a cavity is usually introduced at the antenna's bottom, but it will lead to a high profile and destroy the bidirectional radiation of the design. In this article, a CP array antenna based on a sequential‐phase (SP) feeding network is taken as an example. Only the projection of the feeding network is preserved, while other conductors on the ground are subtracted. The simulated peak gain of this design is only 5.04 dBic. In order to obtain an ultra‐wideband, a wide AR bandwidth, a moderate gain and a low profile of the antenna, a method of etching a circle of ground around the edge of the substrate is presented to expand the ground into a large irregular area. The measured results show that the proposed design can exhibit a 90.9% 10‐dB impedance bandwidth, a 42.4% (5.2–8 GHz) 3‐dB AR bandwidth, a 7.17 dBic peak gain, and a very low profile of 0.006 λ L . This method is very simple to implement and does not need to modify the original antenna structure. It may be applied to conveniently improve the performance of the bidirectional radiation CP antenna.